IMPLEMENTATION OF THE VILLAGE FINANCIAL SYSTEM (SISKEUDES) IN VILLAGE FINANCIAL MANAGEMENT IN NAGORI PAMATANG ASILOM GUNUNG MALELA SUBDISTRICT SIMALUNGUN REGENCY - sri wardani; Kariaman sinaga; muzayanah Depari (Universitas Dharmawangsa Medan, 2026)
This research aims to analyze the implementation of the Village Financial System (Siskeudes) in village financial management and identify supporting and inhibiting factors in its implementation in Nagori Pamatang Asilom, Gunung Malela District, Simalungun Regency. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through in-depth interviews, observation, and documentation. Research informants consist of Pangulu, Nagori Secretary as Siskeudes operator, Kaur Keuangan, Head of BPD, Village Facilitator, and Head of PMN Gunung Malela District.The research results show that the implementation of the Village Financial Management System (Siskeudes) in Pamatang Asilom Village has been running well in the planning, implementation, and administration stages, as well as reporting and accountability of village finances. The implementation of Siskeudes helps the village government record financial transactions in an orderly manner, compile reports systematically, and increase transparency and accountability in village financial management. However, several obstacles remain in its implementation, including limited internet and VPN networks, power outages, and limited human resources in operating the Siskeudes application. To overcome these obstacles, the village government has undertaken various efforts such as coordinating with village facilitators, participating in training and technical guidance, improving supporting facilities, and conducting regular data backups.Keywords: Implementation, Siskeudes, Village Financial Management, Nagori.